SABERES EMERGENTES: A PESQUISA COM PROFESSORAS INDÍGENAS | Emerging knowledge: research with indigenous teachers (Trabalho & Educação, 2016)
Struggles for identity recognition, observed since the second half of the last century, have led to a destabilization in the political and legal fields, as well as in the epistemic sphere. The monopoly of scientific knowledge is interrogated by analyses regarding the coloniality of knowledge and power, which bring to the fore the epistemological diversity of the world. This article dialogues with this interpretive matter and thematizes interpellations to the research processes according to the dynamics of indigenous identity recognition. It analyzes the displacement of an indigenous invisibility actively produced by denial and stigma by the affirmation of an insurgent presence altering epistemological positioning, with methodological repercussions. It discusses the dilemmas present in the transition from research on indigenous peoples to investigation with indigenous researchers within the Indigenous Educators Intercultural Training Program at the Federal University of Minas Gerais (FIEI/UFMG). Based on the framework of Epistemologies of the South, in particular knowledge translation, the impasses that make gender dialogue and ethnicity an original activity are highlighted. ___As lutas por reconhecimento de identidades observadas a partir da segunda metade do século passado resultaram em desestabilizações no campo político e jurídico e também em âmbito epistêmico. O monopólio do conhecimento científico é interrogado por análises acerca da colonialidade do saber e do poder, as quais trazem à tona a diversidade epistemológica do mundo. Este artigo dialoga com esse conjunto interpretativo e tematiza as interpelações aos processos de pesquisa a partir da dinâmica de reconhecimento de identidades indígenas. Analisa-se o deslocamento de uma invisibilidade indígena ativamente produzida por negações e estigmas para a afirmação de uma presença insurgente a alterar posicionamentos epistemológicos, com repercussões metodológicas. Discutem-se os dilemas da passagem da pesquisa sobre povos indígenas para a investigação com pesquisadores/as indígenas no âmbito do curso de Formação Intercultural de Educadores Indígenas (FIEI/UFMG). Com base no referencial das epistemologias do sul, em particular da tradução de saberes, destacam-se os impasses que fazem da interlocução gênero e etnia uma atividade original.